Clinical profiles of adolescent personality pathology: a latent structure examination of the Semi-Structured Interview for Personality Functioning DSM-5 (STiP-5.1) in a help-seeking sample - Thomson, Madelyn; Cavelti, Marialuisa; Lerch, Stefan; Koenig, Julian; Reichl, Corinna; Mürner-Lavanchy, Ines M.; Wyssen, Andrea; Kaess, Michael (Borderline Personality Disorder and Emotion Dysregulation, 2024)
Despite the introduction of dimensional conceptualisations of personality functioning in the latest classification systems, such as Criterion A of the Alternative Model of Personality Disorders in the DSM-5, heterogeneous clinical presentation of personality pathology remains a challenge. Relatedly, the latent structure of personality pathology as assessed by the Semi-Structured Interview for Personality Functioning DSM-5 (STiP-5.1) has not yet been comprehensively examined in adolescents. Therefore, this study aimed to examine the latent structure of the STiP-5.1, and, based on those findings, to describe any unique clinical profiles that might emerge.
Publikationsdatum: 9. April 2024
Gesehen am 13.08.2024